2018
DOI: 10.1016/j.amjcard.2017.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gender on Unplanned Readmissions After Percutaneous Coronary Intervention (from the Nationwide Readmissions Database)

Abstract: Women who undergo percutaneous coronary intervention (PCI) are at higher risk of adverse outcomes compared with men, but it is unknown whether gender affects early unplanned rehospitalization. We analyzed 832,753 patients who underwent PCI from 2013 to 2014 in the Nationwide Readmissions Database. We compared gender differences in incidences, predictors, causes, and cost of unplanned 30-day readmissions and examined the effect of co-morbidity. A total of 832,753 men and women who survived the index PCI and wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 21 publications
3
15
0
Order By: Relevance
“…This gender-based disparity in readmission is likely related to high burden of comorbidities and older age of presentation in female patients as noted by previously published studies exploring readmission pattern after PCI. 12,40 The risk of readmission based on insurance type is corroborated in our study with an increased risk if the payer source was Medicare/Medicaid. Interestingly, FFR utilization during multivessel PCI did not significantly help in reducing 30-day readmission rates.…”
Section: Discussionsupporting
confidence: 74%
“…This gender-based disparity in readmission is likely related to high burden of comorbidities and older age of presentation in female patients as noted by previously published studies exploring readmission pattern after PCI. 12,40 The risk of readmission based on insurance type is corroborated in our study with an increased risk if the payer source was Medicare/Medicaid. Interestingly, FFR utilization during multivessel PCI did not significantly help in reducing 30-day readmission rates.…”
Section: Discussionsupporting
confidence: 74%
“…(i.e., non-Hispanic, Hispanic, and unknown/declined/other), primary language (i.e., English vs. other), marital status (i.e., partnered vs. single), and insurance type (i.e., commercial, Medicare, Medicaid, dual-eligible for Medicare and Medicaid, and other public insurance). Prior studies have found that these variables are associated with increased risk of readmission [35][36][37][38]. For patients with missing race/ethnicity information in the EHR data, we coded their race/ethnicity as "unknown" as a separate category.…”
Section: Plos Onementioning
confidence: 99%
“…There is a growing interest in the study of sex differences in readmissions after cardiovascular procedures such as PCI, TAVI and catheter ablation for AF. [13][14][15] However, no study has examined these differences amongst those undergoing de novo CIED implantation. Despite the baseline differences in patients undergoing each type of procedure, sex disparities in rates and causes of readmissions have been previously observed.…”
Section: Discussionmentioning
confidence: 99%